Decrease in peripheral type 1 over type 2 T cell cytokine production in patients with rheumatoid arthritis correlates with an increase in severity of disease - van Roon, J. A G (1997)
Objectives—To compare peripheral type 1 (T1) and type 2 (T2) T cell activities in rheumatoid arthritis (RA) patients with that found for osteoarthritic (OA) patients and healthy controls and to correlate peripheral T1/T2 cell activity in RA with parameters of the disease. METHODS—Peripheral blood mononuclear cells were isolated from patients with RA (n=66), OA (n=19), and healthy controls (n=15). Primary T cell activity in these mononuclear cells was enhanced by means of anti-CD3/anti-CD28, which mimicks stimulation of T cells by activation of the T cell receptor and a major co-stimulatory signal. Interferon gamma (IFNγ) production and interleukin 4 (IL4) production in the three groups were quantified as measures of T1 and T2 cell activity, respectively, and compared. Serum tumour necrosis factor α (TNFα), erythrocyte sedimentation rate (ESR), C reactive protein (CRP), and joint destruction assessed radiographically of RA patients were determined as parameters of disease activity and correlated with T1/T2 cell activity. RESULTS—Peripheral T cells from RA patients produced significantly less IFNγ and more IL4 than T cells from both age and sex matched OA patients and healthy controls. Moreover, in RA patients both a decrease in IFNγ and an increase in IL4 production correlated with an increase in serum TNFα, ESR, CRP, and joint destruction.  Conclusions—These results suggest a role for differential T cell activity in RA. In view of the intra-articular T1 cell predominance the results might be explained by selective T1 cell migration into the joint or peripheral suppression of T1 cell activity.